Hubungan Kelengkapan Informasi Dengan Persetujuan Klaim Bpjs Di RSUD Kabupaten Sukoharjo Tahun 2016 - Noviasari, Tri; , SRI SUGIARSI, SKM., M.Kes; , YULI KUSUMAWATI, SKM., M.Kes (2016)
Completeness of medical record documents is very important. Medical record serves as proof of valid owned by each patient and legally defensible. Therefore, a complete medical record must be filled out completely and clearly about all the services provided to patients. Incomplete diagnosis codes / actions which contains the medical records of patients will affect the process of determining the claims BPJS. Preliminary studies indicate that they found a 5-7 document medical records have failed to claim every day although already qualified to the verifier, but still there is the possibility of having failed to claim support for attachment file is not complete. This study aimed to analyze the relationship between the completeness of the information in the medical record documents with the consent of claims BPJS in Sukoharjo District Hospital. The study was observational with cross sectional approach. The population in this study is a document medical records of patients hospitalized nonsurgical april dependents BPJS in Sukoharjo District Hospital. The research sample as many as 138 documents specified by consecutive sampling technique. The research instrument is a checklist sheet. Research data analysis using Chi Square. The results showed a significant relationship completeness of the information with the consent of the patient claims BPJS in Sukoharjo District Hospital with a value of p = 0.001.